NEEDS ANALYSIS OF ENGLISH ON INFORMATION SYSTEMS DEPARTMENT STUDENTS USING AN INTEGRATED APPROACH - Fa'adhilah, Wafiyah Asyifah; Jannah, Izzatul; Zamhir, Nabila; Azhar, Nurhumaida; Musafar, Muh. Aqil (University of Darussalam Gontor, 2023)
In order to further comprehend the demands of students studying information systems while learning English, this study presents relevant facts. The focus of this research is investigating the students’ responses to the questions in sections 1) present situation analysis, 2) target situation analysis, and 3) learning needs. The design of this research is a survey using an integrated method. The sample of this research was 10 out of 53 second-year information systems students selected randomly. An online questionnaire survey was used in this study to gather data. Using a quantitative methodology, outcomes analysis was completed. The study's findings demonstrate the importance of English for future career support and competency enhancement. Students require more cutting-edge and visible audio-visual teaching techniques because of this.